Bilateral breast metastases from rectal malignant melanoma: case report and literature review - Liu, Hui; Liu, Qian; Zhang, Linshen; Liu, Qinghua; Cheng, Hao; Liao, Jian; Chen, Zhaohong; Lu, Dingyu (Frontiers in Oncology, 2025)
Rectal melanoma is an extremely rare and highly aggressive disease, and rectal melanoma metastasis to the breast is rare. This is a 48-year-old female who presented with rectal melanoma carcinoma Following the diagnosis of locally advanced rectal cancer (TxN3M0), she received chemotherapy, immunotherapy with radiotherapy, and metastases to the lung, bone and vulvar developed during the therapy. After one year of treatment, the patient developed bilateral breast metastases. Then breast site was identified using the gene expression assay which showed KIT mutation, indicating sensitivity to imatinib, so the patient had used imatinib for 2 months. But then the patient started to take Chinese medicine for personally reason. Sadly, the patient passed away 22 months after initial diagnosis due to rapidly progressive disease. This case showed a rare presentation of rectal melanoma metastasis to the breast. To our knowledge, this is also the first report of rectal melanoma metastasis to bilateral breasts.